AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN TULAK (Schefflera elliptica (Blume) Harms) TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli: Antibacterial Activity of Ethanol Extract of Tulak Leaves (Schefflera elliptica (Blume) Harms) Against Staphylococcus aureus and Escherichia coli - Ni Putu Saraswati Kristina; Aryasa, I Wayan Tanjung; Desak Putu Risky Vidika Apriyanthi (Universitas Tidar, 2023)
Tulak plant is a type of plant that commonly used as a traditional ceremonies and traditional medicine. The purpose of this study was to determine the content of secondary metabolites in tulak leaves (Schefflera elliptica (Blume) Harms) and antibacterial activity against Staphylococcus aureus and Escherichia coli. The extraction method used is the maceration method and for the antibacterial test using the well method. The results of the phytochemical screening test on tulak leaves contain saponins, tannins, phenols and alkaloids. The results of the antibacterial activity test against Staphylococcus aureus at concentrations of 25%, 50%, 75% and 100% respectively had inhibition zones of 6.10±0.05 mm, 7.15±0.03 mm, 8.12±0 .04 mm, and 9.07 ± 0.05 mm which are categorized as moderate. The results of the antibacterial activity test against Escherichia coli at concentrations of 25%, 50%, 75% and 100% respectively did not show the formation of an inhibition zone so value was 0.00±0.00 mm. The conclusion from this study is that tulak leaves (Schefflera elliptica (Blume) Harms) have antibacterial activity against Staphylococcus aureus but do not have antibacterial activity against Escherichia coli.